Outcomes in Patients With Lung Adenocarcinoma With Transformation to Small Cell Lung Cancer After EGFR Tyrosine Kinase Inhibitors Resistance: A Systematic Review and Pooled Analysis - Xu, Jinhe; Xu, Lihuan; Wang, Baoshan; Kong, Wencui; Chen, Ying; Yu, Zongyang (Frontiers in Oncology, 2022)
Background Lung adenocarcinoma can transform into small-cell lung cancer (SCLC) when resistance to tyrosine kinase inhibitors (TKIs) develops. Approximately 3% to 10% of epidermal growth factor receptor (EGFR) -mutant non-small cell lung cancer (NSCLC) could transform to SCLC. This phenomenon has been described in several case reports and small patient series. However, the characteristics and treatment outcomes of this population have not been comprehensively reported, and their clinical course is poorly characterized. Methods We performed a systematic review of the published literature to summarize the clinical and pathological features and prognosis of the reported cases and analyzed the demographics, disease features, and outcomes. Results 72 patients initially diagnosed with lung adenocarcinoma were included, 50 females and 22 males. EGFR mutations included 19-deletion (75%), L858R (22%), and G719X (3%). All patients received EGFR-TKIs before SCLC transformation. The median time from diagnosis to transformation was 20.5 months (95% CI, 15.45 to 26.55 months). Of the 67 patients with post-translational gene test results, 58 maintained their EGFR mutation, and only 1 of 18 with prior T790M positivity retained T790M mutation. After the pathological transformation, both conventional chemotherapy regimen and chemotherapy combined targeted therapy yielded high response rates. The disease control rate of first-line therapy after transformation was 76%, while the objective response rate was 48%. The median overall survival (OS) since diagnosis was 27 months (95% CI, 22.90 to 31.10 months), whereas median OS since SCLC transformation was 8.5 months (95% CI, 5.50 to 11.60 months). Conclusion The prognosis of transformed SCLC is worse than primary SCLC. The response rate to conventional chemotherapy was high. However, the progression-free survival and OS after transformation were short and the prognosis was poor with first-line therapies. New therapies are needed in the management of transformed SCLC.